Visual and Olfactory Cues with Nectar Accessibility: Drivers of Floral Selection in Sycanus annulicornis (Hemiptera: Reduviidae) - Wildan Muhlison; Zulfa Maulida; Irwanto Sucipto; Hari Purnomo (Bogor Agricultural University, Indonesia, 2026)
Sycanus annulicornis (assassin bug) is a potential predator of agricultural pests in soybean, rice, vegetable, and plantation crops. However, habitat degradation has reduced its population and effectiveness as a biological control agent. This study aimed to evaluate the floral selection of S. annulicornis based on visual and olfactory cues, as well as nectar accessibility. Behavior observations were conducted using choice and non-choice tests to assess visitation rates to different flower colors and plant species. The results showed a broad color preference, with the highest visitation rates to white (2.00 ± 0.82) and yellow (1.75 ± 0.63) flowers. In non-choice tests, the highest visitation percentages were recorded on Tagetes erecta (82%), Turnera subulata (80%), Turnera ulmifolia (73%), and Wedelia trilobata (67%). In choice tests, T. subulata was the most attractive plant, followed by T. ulmifolia, T. erecta, and W. trilobata. Floral morphological compatibility, particularly nectar accessibility, supported the utilization of supplementary food resources by S. annulicornis. These findings suggest that selecting appropriate flowering plants can be an effective conservation strategy to enhance the sustainability of S. annulicornis populations in agroecosystems.